2014
DOI: 10.1002/2013jc009274
|View full text |Cite
|
Sign up to set email alerts
|

Large‐scale impact of Saharan dust on the North Atlantic Ocean circulation

Abstract: The potential for a dynamical impact of Saharan mineral dust on the North Atlantic Ocean large-scale circulation is investigated. To this end, an ocean general circulation model forced by atmospheric fluxes is perturbed by an idealized, seasonally varying, net shortwave flux anomaly, as it results from remote sensing observations of aerosol optical thickness representing Saharan dust load in the atmosphere. The dust dynamical impact on the circulation is assessed through a comparison between perturbed and an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…A recent modeling study that examined transport pathways of dust to the Northeast United States showed that the majority of plumes reside between 2 to 6 km but urged that more observational data are needed to examine vertical dust structure (Zhang et al, ). Dust is thought to have the potential to impact the North Atlantic Ocean circulation, specifically large‐scale barotropic and overturning circulations (Serra et al, ). These large‐scale phenomenon that may have sensitivity to dust certainly require more investigation owing to their importance for the region's climate system and ocean processes.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…A recent modeling study that examined transport pathways of dust to the Northeast United States showed that the majority of plumes reside between 2 to 6 km but urged that more observational data are needed to examine vertical dust structure (Zhang et al, ). Dust is thought to have the potential to impact the North Atlantic Ocean circulation, specifically large‐scale barotropic and overturning circulations (Serra et al, ). These large‐scale phenomenon that may have sensitivity to dust certainly require more investigation owing to their importance for the region's climate system and ocean processes.…”
Section: Synthesis Of Results and Future Outlookmentioning
confidence: 99%
“…Other researchers have emphasized the importance of aerosol cooling as a forcing of the North Atlantic and in some cases, its influence on the AMOC, both in models and in observations on the multidecadal time scale. Swingedouw et al () and Pausata et al () reported on the influence of volcanic aerosols on solar radiation and the North Atlantic overturning circulation, while Booth et al (), Cowan and Cai (), and Serra et al () all emphasized the importance of tropospheric aerosol forcing on cooling the North Atlantic. The Booth et al () study is particularly relevant, as they found that in their model, it was the indirect forcing effect of aerosols that allowed them to more closely match the multidecadal variability in North Atlantic SSTs.…”
Section: Discussionmentioning
confidence: 99%
“…Estimates of dust emission from the arid regions of North Africa are about 800 Tg yr À1 of soil material that accounts for 70% of the global total and it is six times higher than the next largest source, from Asia (e.g., Huneeus et al, 2011;Prospero and Mayol-Bracero, 2013). The dust mobilized over Northern Africa is transported over the Mediterranean and southern Europe (e.g., Avila and Alarc on, 1999;Goudie and Middleton, 2001;Rodríguez et al, 2001;Escudero et al, 2005;Querol et al, 2009;Marconi et al, 2014), and also across the Atlantic (e.g., Prospero et al, 1995Prospero et al, , 1999Caquineau et al, 1998;Alastuey et al, 2005;Gangoiti et al, 2006;Moreno et al, 2006;Serra et al, 2014). In the Mediterranean regions, the amount of Sahara dust deposition varies depending on atmospheric trajectories and distance from the source.…”
Section: Aeolian Inputsmentioning
confidence: 99%